Odoo 12 Development Cookbook : 190+ unique recipes to build effective enterprise and business applications, 3rd Edition /: 190+ unique recipes to build effective enterprise and business applications, 3rd Edition. (2019) - Gajjar, Parth; Fayolle, Alexandre; Brunn, Holger; Reis, Daniel
No abstract available